Overheating assessment in Passivhaus dwellings: the influence of prediction tools - Vitor Leite Goncalves; Vincenzo Costanzo; Kristian Fabbri; Tarek Rakha (Buildings & Cities, 2022)
Thermal comfort during the summer in the Passivhaus concept relies mainly on natural ventilation to provide indoor cooling. Do airflow modeling tools accurately predict overheating in summer and for anticipated warmer climates? What effect do simplifications of airflow modeling techniques have on the overheating assessment of Passivhaus dwellings? Measured data and a calibrated thermal model are employed in the present study to address this question. The calibrated model is then used to create a standalone building energy model (BEM), a BEM coupled with an airflow network model (AFN), and a BEM coupled with an AFN supported by the wind pressure coefficients obtained from computational fluid dynamics (CFD) simulation. The outcome of each modeling approach was then compared against each other within three different European climates. Results showed that the overheating frequency prediction found with the default design infiltration and natural ventilation inputs commonly used in the literature agreed fairly with those obtained from the AFN + CFD in temperate or colder climates (< 2% difference), but were significantly underestimating overheating in Passivhaus buildings located at warmer climates (9.4% difference). For Passivhaus dwellings in warmer climates, the airflow modeling approach is unlikely to provide for an accurate estimation of the overheating incidence. 'Practice relevance' With overheating becoming a major issue in Europe, the prediction of the indoor thermal performance by using dynamic building simulations became common practice by researchers and practitioners. This study scrutinized the three most common methods of modeling airflow phenomena (BEM, AFN and CFD) when performing building energy simulations. For Passivhaus buildings located in warmer climates, the choice of airflow modeling approach is important to obtain an accurate prediction of overheating. The study found that BEM is unlikely to be suitable for predicting the extent and frequency of overheating in home and warm climates. The AFN + CFD approach provides a more reliable approach for predicting overheating in hot and warm summer climates. For Passivhaus homes in locations with cooler summers, the difference between modeling approaches became mostly insignificant, so the simpler BEM models may be sufficient when performing an overheating analysis in that context.